Heterozygosity, genetic similarity and extra‐pair paternity variation in two populations of rock sparrow Petronia petronia: a within and between populations comparison. (13th March 2022) - Corregidor‐Castro, Alejandro; Griggio, Matteo; Grapputo, Alessandro; Mingozzi, Toni; Pilastro, Andrea; Plaza, Mireia; Cantarero, Alejandro
Abstract : Extra‐pair paternity (EPP) has been broadly reported in socially monogamous bird species and it has been hypothesized that females engage in extra‐pair copulations to increase the genetic variability of the offspring and to reduce the risk of inbreeding and genetic incompatibilities. This hypothesis makes two predictions: within populations, females should engage with more dissimilar/heterozygous males and, among populations, females should pursue more frequently EPP in populations characterized by a lower genetic variability and a higher homozygosity. However, support is still unclear throughout literature, and usually involves the study of a single population. We compared a peripheral population of rock sparrow Petronia petronia living at the marginal distribution of the species and characterized by a high EPP level (> 50%) (Italian Alps) with a population located in the centre of the species' distribution (central Spain), to understand if variations in EPP could be linked to differences in mean heterozygosity and genetic similarity both between and within populations. EPP in the Spanish population was 18.1%, three times lower than that observed in the Alpine one (51.2%), and this difference remained fairly constant across different years. Supporting the between populations prediction, we found lower heterozygosity and reduced allelic richness in the Alpine population compared to the Spanish one. In contrast, social and extra‐pair males, as well as within and extra‐pair offspring, did not significantly differ in terms of genetic similarity and heterozygosity within brood in either population. Social and extra‐pair males did not differ in tarsus size, body weight or yellow badge size, suggesting that females were not choosing extra‐pair partners based on heterozygosity, genetic similarity or phenotypic quality. Although based on a limited sample in the within population analysis, our results indicate that EPP may evolve in response to a low level of genetic variability in the population.